Controlled Synchronization by Limited Capacity Communication Channel - Ziqi Dong; Yongchun Liu; Da Lin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The work focuses on synchronization of time-delay chaos systems under information constraints. A theoretical analysis for time-delayed system by limited communication channel is provided. By using the Lyapunov-Krasovskii approach, a synchronization condition is first obtained. Encoder of binary coding is designed by this condition, and synchronization error of this systems tends to zero. Finally, analytical conditions are used for synchronization of time-delay chaos systems under information constraints, and simulations verify the validity of obtained result.